2011
DOI: 10.1037/a0021766
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves executive function and achievement and alters brain activation in overweight children: A randomized, controlled trial.

Abstract: Objective This experiment tested the hypothesis that exercise would improve executive function. Design Sedentary, overweight 7- to 11-year-old children (N = 171, 56% female, 61% Black, M ± SD age 9.3 ± 1.0 yrs, body mass index (BMI) 26 ± 4.6 kg/m2, BMI z-score 2.1 ± 0.4) were randomized to 13 ± 1.6 weeks of an exercise program (20 or 40 minutes/day), or a control condition. Main outcome measures Blinded, standardized psychological evaluations (Cognitive Assessment System and Woodcock-Johnson Tests of Achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
631
11
26

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 710 publications
(705 citation statements)
references
References 70 publications
37
631
11
26
Order By: Relevance
“…activity improves cardiorespiratory fitness and mood and results in brain changes [4]. Regular physical activity improves executive function, and acute bouts improve attention and time on task [3,18].…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…activity improves cardiorespiratory fitness and mood and results in brain changes [4]. Regular physical activity improves executive function, and acute bouts improve attention and time on task [3,18].…”
Section: Researchmentioning
confidence: 99%
“…Regular physical activity improves cognitive function, induces brain changes, and improves mood in children, in addition to improving their aerobic fitness [3][4][5][6][7][8]. Greater aerobic fitness and physical activity are associated cross sectionally with increased grade point averages and standardized test scores [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We do note, however, that our sample size and/or participation rate are consistent with prior exercise trials in children. 15,16,32 Because of our relatively small sample size and that our sample of healthy children was only assessed at a single time point, our ability to determine whether the observed training effects reflects normal brain growth is limited. Further, we did identify selection bias in recruitment: we found that patients and families who needed to travel longer periods of time to participate in group sessions were underrepresented in our sample (see Supplemental Material online).…”
Section: Neurooncologymentioning
confidence: 99%
“…11 Clinical trials have demonstrated that aerobic exercise training can foster brain growth, slow cognitive decline in normal and pathological aging, [12][13][14] and enhance brain and cognitive function in healthy and obese children. 15,16 Given the promising results linking exercise with brain health, it is surprising that limited work has examined its therapeutic effects for brain recovery in pediatric brain tumor survivors. Although exercise training has been linked to improved cognitive performance in adults with traumatic brain injury, stroke, and multiple sclerosis, these trials have not assessed changes in the brain.…”
Section: Neurooncologymentioning
confidence: 99%
“…Although the TTM has been shown to be effective in promoting physical activity across various populations including children/adolescents [3], adults in the general population [4], and adults with chronic disease [5], it is plausible that executive function may moderate the utility of the TTM in predicting physical activity. This plausibility stems from the fact that the previous research demonstrates that executive function improvement is associated with increased physical activity [6] and decreased sedentary behavior [7]. Executive functioning (EF) is defined as managing cognitive processes including working memory, cognitive flexibility, response selection, planning, and execution of tasks [8].…”
Section: Introductionmentioning
confidence: 99%